Edukasi dampak negatif minuman berenergi bagi anak-anak dan remaja di SMP Muhammadiyah 2 Kota Ternate - Abdullah, Abulkhair; Disi, Muhammad Zulfian A. (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
Energy drinks have become increasingly popular recently, especially among children and adolescents. According to the survey, adolescents are the largest consumers of energy drinks. Due to the lack of knowledge among parents and the public regarding the adverse effects of energy drinks, supervision of energy drink consumption among children and adolescents is uncontrolled. Therefore, education for children and adolescents needs to be done regularly. This activity was carried out at SMP Muhammadiyah 2 Ternate City. The targets of this activity are students in grades VII, VIII, and IX. The stages in implementing this activity consist of determining the activity's location, observing the activity's location, planning the program, preparing the material, implementing the activity, and evaluating it. Activities were carried out through counseling (lectures and discussions) about the adverse effects of energy drinks on children and adolescents. The activities were evaluated using pre-test and post-test questionnaires. The results showed that students' understanding of the counseling material increased significantly (P < 0.000) with average pre-test and post-test scores, 30.95 Â± 15.05 and 61.43 Â± 18.05, respectively.